2015
DOI: 10.1016/j.molonc.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo transducer TAZ promotes epithelial to mesenchymal transition and cancer stem cell maintenance in oral cancer

Abstract: The Hippo pathway has emerged as a fundamental regulator in tissue growth, organ size and stem cell functions, and tumorigenesis when deregulated. However, its roles and associated molecular mechanisms underlying oral squamous cell carcinoma (OSCC) initiation and progression remain largely unknown. Here, we identified TAZ, the downstream effector of Hippo signaling, as a novel bona fide oncogene by promoting cell proliferation, migration/invasion and chemoresistance in OSCC. TAZ promoted epithelial-to-mesenchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
141
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 147 publications
(144 citation statements)
references
References 58 publications
3
141
0
Order By: Relevance
“…In neuroblastoma cell lines, studies have shown how TAZ upregulates connective tissue growth factor (CTGF) known to induce EMT (19). Moreover, in oral cancer cells, TAZ has also been found to be involved in TGF-β1 induced EMT (20). …”
Section: Clinical-translational Advancesmentioning
confidence: 99%
See 1 more Smart Citation
“…In neuroblastoma cell lines, studies have shown how TAZ upregulates connective tissue growth factor (CTGF) known to induce EMT (19). Moreover, in oral cancer cells, TAZ has also been found to be involved in TGF-β1 induced EMT (20). …”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…Interestingly, the SREBP/mevalonate cascade is needed to activate RhoGTPase. As this metabolic pathway is inhibited by statins, simvastatin has also been reported to repress TAZ, leading to potent anti-cancer effects (20, 59). …”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…Dysregulation of Hippo pathway and hyperactivation of WWTR1 and YAP1 essentially have been proved in promoting cancer outgrowth, locoregional recurrence and metastatic spreading . Notably, mounting evidence support that WWTR1 as a putative oncogene was commonly overexpressed in multiple cancers such as breast cancer, lung cancer, papillary thyroid carcinoma, and HNSCC . Given the facts that WWTR1‐AS1 is a NAT corresponding to the 5′‐UTR of WWTR1, we addressed the hypothesis that WWTR1‐AS1 modulated cell phenotypes by regulating WWTR1 in HNSCC by experimental and bioinformatics approaches.…”
Section: Discussionmentioning
confidence: 99%
“…A key enzyme in this pathway is 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase, which is inhibited by statins. Statin treatment caused cytoplasmic relocalization and inhibition of YAP/TAZ in several cancer types and a reduction of cancer stem cell growth and tumor xenografts (Sorrentino et al, 2014;Wang et al, 2014;Li et al, 2015). Bisphosphonates and geranylgeranyl transferase 1 inhibitors also target the mevalonate pathways and have similar effects on inhibiting YAP and TAZ (Sorrentino et al, 2014;Mi et al, 2015).…”
Section: Targeting Mechanotransduction Pathways In Cancermentioning
confidence: 99%
“…Low toxicity in phase 1 trials, some disease stabilization YAP/TAZ inhibition and cytoplasmic relocalization; reduction in cancer stem cell growth and tumor xenograft models Sorrentino et al, 2014;Wang et al, 2014;Li et al, 2015 Verteporfin YAP/TAZ inhibitor Inhibits YAP-TEAD binding and suppresses downstream signaling in retinoblastoma Liu-Chittenden et al, 2012;Brodowska et al, 2014;Wang et al, 2015 Dasatinib Src inhibitor Monotherapy phase 2 trials show some effect in breast and prostate cancer and melanoma, and no benefit in other cancer types such as small cell lung cancer; combination in with statin treatment has a greater effect on downstream YAP/TAZ activity Mayer and Krop, 2010;Miller et al, 2010;Rosenbluh et al, 2012;Calvo et al, 2013;Taccioli et al, 2015 HMG-CoA, 3-hydroxy-3-methyl-glutaryl-coenzyme A; GIST, gatrointestinal stromal tumor.…”
Section: Targeting the Ecm Components In Cancermentioning
confidence: 99%